Technology Entrepreneurship (ENT 600) Bullet Pen / Ahmad Aiman Haikal Jenuwa … [et al.] - Jenuwa, Ahmad Aiman Haikal; Mohd Nor, Mohd Syamsul Bakri; Mohd Tajul Hasnan, Mohd Tajul Izrin; Kamarudin, Nor Karimah; Ramli, Siti Aishah (2015)
The team is introducing a bullet pen, which is a single pen with multipurpose bullets that enables the user to use a single tool for multipurpose tasks. The team has discussed and observed the priority needs of a man's stationery. People need tools to do their work that includes many different items such as pencil, pen, thumb drive or laser pointer and etc. Sometimes, there are too much tools that could be reached by the grab of their hands. Therefore, our tedm is proposing a solution where different tools are included into a single pen: A Bullet Pen (with multipurpose bullet).